Clinopathological assessment of epulis lesions from Sindh Pakistan - Surwaich , Arhama; Channa, Surwaich Ali; Iqbal, Waqas; Majid , Abdul; Ahmed , Arsalan; Fida Baloch (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVES: Gingival enlargement is a common characteristic of gums infection. Enlargement of the gums can possibly occur due to numerous factors, comprising of inflammatory disorders as well as certain meditational side effects. Pyogenic granuloma expresses as red, small erythematous papules on pedunculated or rather sessile base. The current study aims to evaluate the cases of epulis and to grade histological types of epulis. METHODOLOGY: This descriptive cross-sectional study was carried out at oral surgery OPD ISRA Dental College for a six-month duration. The diagnosis of epulis was made on the basis of clinical and histological examination. The research data was recorded on pre-designed proforma, and data were analyzed using SPSS version 22.0 (IBM, Corporation). RESULTS: Out of 150 study subjects, 90 (60%) patients were female, while 60 (40%) were male. Majority of the cases in our study were found with a maxillary site (n=93, 62.0%). Most had a size of 2cm-3cm (n=132, 76%). Coral Pink color was the most common in (n=90, 60%) patients, followed by red color (n=45, 30%) and pale color was found in (n=15,10%) of the cases. The histological findings proved pyogenic granuloma was most common in (n=75, 50%) of the cases followed by fibrous epulis (n=63, 42%), peripheral giant cell granuloma (n=6, 4%) and Peripheral ossifying fibroma (n=6, 4%). CONCLUSION: Pyogenic granulomas are the most prevalent reactive lesion. The lesions were more common in females in maxilla portion, and they were mostly found in the second to third decade of life.